Tourist Perception of Visitor Management Strategy in North Bandung Protected Area - Ervina, Ersy; Wulung, Shandra Rama Panji; Octaviany, Vany (Institut Pariwisata dan Bisnis Internasional, 2020)
Sustainable tourism is one of Djuanda Forest Park (Tahura) management goals in implementing a visitor management strategy in the North Bandung Protected Areas. Djuanda Forest Park is an important area to be preserved as a tourist destination because of its very strategic function for environmental sustainability in Bandung City and its buffer areas. The visitor management strategy's implementation level can be seen from the perception of tourist who comes to Djuanda Forest Park, which analyzes by the intensity of destination use, accessibility, and carrying capacity. Perception cannot be separated from the satisfaction of tourists when visiting. This study aims to analyze tourists' perceptions of the implementation of visitor management strategies together with tourist satisfaction in the Tahura protected area. The method used is descriptive with data collection techniques through questionnaires. The results showed that tourist perceptions and satisfaction with the Visitor Management Strategy application were quite good. In improving quality, management is expected to be able to design a more systematic flow of visits and limit the number of visits for each tourist area to minimize the impact of tourism activities on the environment. On the satisfaction side, managers need to improve product and service quality, especially the preservation of tourist areas to create tourists experience